The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/dth.12056
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-induced adult colloid milium treated with fractionated CO2laser

Abstract: Adult colloid milium is a rare cutaneous deposition disorder that frequently involves areas of chronic sun exposure. The most common clinical presentation exhibits multiple, firm, and amber-colored papules that cluster to form large plaques. Histologically, there are masses of amorphous, eosinophilic material expanding the papillary dermis, and at times extending into the mid-dermis, with adjacent solar elastosis. When this disorder affects the face, disfiguring is of great concern and treatment is often sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
4
1
Order By: Relevance
“…Li et al first used of fractionated CO 2 laser to treat these lesions, achieving clinical clearance and no recurrence at the three month follow up. 18 In contrast, there was a minimal response to fractional CO 2 laser in our case owing to the depth of lesions unreached by this mode. Meanwhile, a marked difference was observed using the surgical CO 2 laser as most lesions were mostly ablated and achieved complete epithelization within two weeks.…”
Section: Treatmentcontrasting
confidence: 57%
“…Li et al first used of fractionated CO 2 laser to treat these lesions, achieving clinical clearance and no recurrence at the three month follow up. 18 In contrast, there was a minimal response to fractional CO 2 laser in our case owing to the depth of lesions unreached by this mode. Meanwhile, a marked difference was observed using the surgical CO 2 laser as most lesions were mostly ablated and achieved complete epithelization within two weeks.…”
Section: Treatmentcontrasting
confidence: 57%
“…Gomes reported that photodynamic therapy utilizing methyl aminolevulinate prior to vigorous curettage was useful in two cases, with no recurrences noted after 1 year . Treatment with a fractionated CO 2 laser has also been reported to produce a good therapeutic outcome lasting many months . Our patient has been treated with CO 2 laser, which led to satisfactory outcome after two sessions (Figure ).…”
Section: Discussionmentioning
confidence: 58%
“…Gomes et al 10 report two cases in which they used photodynamic therapy with methyl-aminolevulinate cream as photosensitizer prior to curettage, with no recurrence at the 1-year follow-up visit. Li et al 11 used a fractionated CO 2 laser, obtaining adequate results over a 3-month follow-up.…”
Section: Discussionmentioning
confidence: 99%